Análise do teor de compostos bioativos do capim-santo (cymbopogon citratus) in natura e sob extrato de infusão - MARTINS, Thielly Ribeiro (2024)
Plants with functional activities play a crucial role in both the biological diversity of our planet and our own lives. The lemongrass (Cymbopogon citratus), recognized for it's functional properties and abundance of bioactive compounds with various health benefits, such as preventing non-communicable chronic diseases, is widely known and utilized by the population in culinary preparations. This includes using the plant in it’s natural form as a seasoning in culinary recipes or as a tea. The aim of this study is to compare the bioactive compounds of lemongrass in its natural state and as an infusion extract. Regarding the methodology, procedures for leaf selection and drying were conducted for the physical-chemical and phytochemical analyses of the sample. The leaves of lemongrass in their natural state exhibited 78.11 mg GAE/g (phenolic compounds), 69.46 mg/g (flavonoids), 18.29 mg/g (anthocyanins), 2.51 μg/100g (chlorophyll a), 3.27 μg/100g (chlorophyll b), and 17.11 mg/100g (vitamin C). In the infusion extract sample, values of 23.25 mg GAE/g of phenolic compounds, 1.32±0.102 mg/g of flavonoids, 0.65±0.131 mg/g of anthocyanins, 0.019±0.002 μg/100g of chlorophyll a, 0.021±0.001 μg/100g of chlorophyll b, and 4.53±1.515 mg/100g of vitamin C were obtained. Fourier-transform infrared (FTIR) analysis showed the presence of functional groups related to fibers in the material. In conclusion, lemongrass is a nutritionally rich medicinal herb, showcasing significant levels of bioactive compounds that may undergo degradation or experience an increase in bioaccessibility through the thermal infusion process.